The automated system for collection, processing and transmission of data for training and competitive process in ski jumping - Kiesewetter, D.; Korotkov, K.; Malyugin, V. (8th Conference on Internet of Things and Smart Spaces, 2015)
It is described the system of collection, transmission and processing of data necessary for the organization of competitions and training process on jumps on skis from a springboard that contains the wireless data collection network with judges panels, wireless system remote control start, wired network data collection from sensors of landing and as well as an automated system for determining the distance of a jump on skis from a springboard. Typical signals obtained from the sensors of landing are shown. It is noted that the main problems in automatic detection-range jumps are: different speed of sound propagation in the coating springboard, non-point sound source, and other factors. The experience of designing and operation of this system are represented.